2020
DOI: 10.1186/s12933-020-01022-7
|View full text |Cite
|
Sign up to set email alerts
|

Report from the 5th cardiovascular outcome trial (CVOT) summit

Abstract: The 5th Cardiovascular Outcome Trial (CVOT) Summit was held in Munich on October 24th-25th, 2019. As in previous years, this summit served as a reference meeting for in-depth discussions on the topic of recently completed and presented CVOTs. This year, focus was placed on the CVOTs CAROLINA, CREDENCE, DAPA-HF, REWIND, and PIONEER-6. Trial implications for diabetes management and the impact on new treatment algorithms were highlighted for diabetologists, cardiologists, endocrinologists, nephrologists, and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…[ 14 , 15 ] CVOTs, most of which are pragmatic RCTs, play a key role in the development of clinical practice guidelines for diabetes. [ 9 , 16 19 ] However, recent studies have reported that CVOTs do not adequately represent real-world patient populations. [ 20 , 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 , 15 ] CVOTs, most of which are pragmatic RCTs, play a key role in the development of clinical practice guidelines for diabetes. [ 9 , 16 19 ] However, recent studies have reported that CVOTs do not adequately represent real-world patient populations. [ 20 , 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…As in previous years [ 33 37 ], we present and summarise key aspects discussed at the sixth edition of the CVOT Summit in October 2020, which was the first to be held virtually. The CVOT Summit—Cardiovascular and Renal Outcomes 2020 was an interdisciplinary platform, which was also organized in conjunction with four study groups: Primary Care Diabetes Europe (PCDE, www.pcdeurope.org ), European Diabetic Nephropathy Study Group (EDNSG, www.ednsg.org ), the Incretin Study Group ( www.easd-incretin.ku.dk ), and the Working Group Diabetes & Herz ( www.ddg.org ).…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of cardiovascular disease is a major objective of diabetes care [ 1 ]. In the past decade, cardiovascular outcome trials (CVOTs) have been performed in patients with type 2 diabetes (T2D) with the primary aim of demonstrating safety of glucose lowering medications (GLMs) concerning the risk of cardiovascular events [ 2 , 3 ]. Some of these CVOTs were designed to test superiority and some eventually found lower rates of cardiovascular events among patients randomized to active GLM compared to those randomized to placebo plus standard care [ 4 ].…”
Section: Introductionmentioning
confidence: 99%